Production of high titered immunoreactive serum against FMDV - DECHAMMA, H J; KUMAR, C ASHOK; NAGARAJ, G; REDDY, G R; SURYANARAYANA, V V S (The Indian Journal of Animal Sciences, 2011)
Currently inactivated purified foot-and-mouth disease virus of various serotypes are used to raise type specific sera, which is laborious and involves the risk of handling live virus. Alternatively immunoreactive proteins produced in heterologous host system are an unlimited source of antigen for the production of diagnostic reagents. However, shorter peptides elicit low antibody titred sera. Hence the present study was taken up to evaluate the immune response ofa nlononler and compare with that ofa tetramer protein carrying inlmunoreactive epitopes ofFMDVserotype'0' .The research attempt of using specific recombinant antigen inmultilner form improve'd the immune response by increasing titre of the serum.Â